Pelaksanaan Pembiayaan Murabahah di Koperasi Syariah Hayatussunnah Masjid Jami Mungsolkanas - Sobarna, Nanang; Lutfadila, Silmi (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
Sharia Cooperatives are financial institutions that run their business based on sharia principles. One of the businesses that are run on Islamic cooperatives, namely financing. So the financing mechanism in Sharia Cooperatives must be in accordance with sharia principles, namely the principles of Islamic law based on fatwas issued by institutions that have authority in determining fatwas in the field of sharia. One of the Sharia Cooperatives that has sharia financing products and businesses is the Hayatussunnah Sharia Cooperative Jami Mungsolkanas Mosque. Of the many types of financing used by members of this sharia cooperative, murabahah financing is used. The purpose of this study was to determine whether the implementation of murabaha financing at Hayatussunnah Sharia Cooperative Jami Mungsolkanas Mosque conforms with the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The research method used in this research is descriptive qualitative method. The implementation of murabahah contract financing at Hayatussunnah Sharia Cooperative Jami Mungsolkanas Mosque in the perspective of the DSN-MUI fatwa can be said to be in accordance with sharia principles. .